On exponential decay properties of solutions of the (3 + 1)-dimensional modified Zakharov-Kuznetsov equation - Gezi Chong; Jianxia He (Electronic Research Archive)
We study here the special decay properties of real solutions to the initial value problem associated with the (3 + 1)-dimensional modified Zakharov-Kuznetsov equation. More precisely, we prove the properties of exponential decay of order $ 3/2 $ above the plane $ x+y+z = 0 $ as time evolves. This property is related with the persistence properties of the solution flow in weighted Sobolev spaces and sharp unique continuation properties of solutions to this problem.